Unveiling Sexsomnia: An In-Depth Exploration - Suharyani, Sally; William (Indonesian Andrology and Biomedical Journal, 2023)
Sexsomnia is one type of parasomnia that can negatively impact the quality of life for individuals affected and potentially lead to legal complications. The growing prevalence of sexsomnia demands attention due to the widespread misinformation and the misconception that it is not a medical issue. This review will delve deeper into sexsomnia, including its diagnosis and management. Parasomnia refers to undesired physical events or experiences that occur during various stages of sleep. Sexsomnia, a form of parasomnia associated with non-rapid eye movement (NREM) sleep, is characterized by unconscious, abnormal sexual behavior. Sexsomnia can manifest during any sleep phase but is most frequently observed during NREM sleep. Clinical manifestations of sexsomnia include vocalizations, fondling, kissing, masturbation, and even engaging in sexual intercourse without recollection upon waking. A comprehensive evaluation, including a thorough medical history and additional investigations such as polysomnography with electroencephalography, aids in establishing a diagnosis of sexsomnia. Presently, there is no definitive treatment for sexsomnia. Management approaches involve non-pharmacological and pharmacological. Sexsomnia, if not recognized as early as possible, can have detrimental effects on both the affected individual and the surrounding environment. Lack of awareness about sexsomnia and hesitation to seek treatment contribute to the lack of information about its prevalence. In-depth knowledge is crucial for accurate diagnosis and determining the appropriate management strategies for this condition. Further research is needed to determine sexsomnia and its management.